ANALISIS PERAN PETANI DALAM PENGELOLAAN AIR IRIGASI - Darwati Susilastuti, Karno, dan Tungga Buana Diana (Fakultas Pertanian Universitas Borobudur, 2018)
Demand for irrigation water will increase in line with toting up cultivation area of rice required in the future. On the other hand, water supply should be allocated to fulfill water demand of non-agricultural sectors which are also steadily increased. It implies that water available for irrigation will be scarcer, and therefore, utilization of irrigation water resources should be carried out in a more efficient way. It might be feasible to apply economic value of the irrigation water as a basis of water pricing. Irrigation water institutions together with farmers, made meet water charges paid by the farmers and the quantity of water used and the marginal value product of the irrigation water. Farmers ability to pay, it implies farmers participation on conservation water resources. Key words: demand, supply, institution, participation, conservation